Toward Efficient Detection of Small Near-Earth Asteroids Using the Zwicky Transient Facility (ZTF). (23rd May 2019) - Ye 叶 泉, Quanzhi 志; Masci, Frank J.; Lin 林 省, Hsing Wen 文; Bolin, Bryce; Chang 章 展, Chan-Kao 誥; Duev, Dmitry A.; Helou, George; Ip 葉 永, Wing-Huen 烜; Kaplan, David L.; Kramer, Emily; Mahabal, Ashish; Ngeow, Chow-Choong; et al.
Abstract: We describe ZStreak, a semi-real-time pipeline specialized in detecting small, fast-moving, near-Earth asteroids (NEAs), which is currently operating on the data from the newly commissioned Zwicky Transient Facility (ZTF) survey. Based on a prototype originally developed by Waszczak et al. (37 ) for the Palomar Transient Factory (PTF), the predecessor of ZTF, ZStreak features an improved machine-learning model that can cope with the 10× data rate increment between PTF and ZTF. Since its first discovery on 2018 February 5 (2018 CL), ZTF/ZStreak has discovered 45 confirmed new NEAs over a total of 232 observable nights until 2018 December 31. Most of the discoveries are small NEAs, with diameters less than ∼100 m. By analyzing the discovery circumstances, we find that objects having the first to last detection time interval under 2 hr are at risk of being lost. We will further improve real-time follow-up capabilities, and work on suppressing false positives using deep learning.